Minimizing patient morbidity after free gingival graft harvesting:A triple‐blind randomized‐controlled clinical trial. Issue 6 (6th April 2022) - Bitencourt, Fernando Valentim; Cardoso De David, Silvia; Schutz, Jasper da Silva; Otto Kirst Neto, Alfredo; Visioli, Fernanda; Fiorini, Tiago
Abstract: Objectives: This study aimed to evaluate the effect of photobiomodulation therapy (PBMT) on patient morbidity and donor site healing after free gingival graft (FGG) harvesting. Methods: Forty‐four patients requiring FGG were selected for this trial. Individuals were randomly assigned to test group (PBMT, n = 22) or control group (placebo, n = 22) applied immediately after surgery, 24 and 48 h after. Demographic, surgical‐related and psychosocial variables possibly associated with treatment response were collected. The primary outcome was postoperative pain at the donor site evaluated using Visual Analog Scale (VAS) immediately after surgery and 6, 24, 48 and 72 h after. Secondary outcomes include medication consumption, patient‐reported outcome measures (PROMs) and percentage of wound closure. Results: Intragroup analysis showed no differences in VASLOG means for placebo group throughout the study ( p > .05), whereas a significant difference in PBMT group at 6 h, 24 h, 48 h and 72 h ( p < .05) were observed. Postoperative rescue analgesic requirement was significantly higher in the placebo group ( p = .004). The number needed to treat(NNT) was 2.43. PBMT group reported significant better function related to sleeping, going to work/school and daily routine activities, less restriction to mouth opening, chewing and food consumption, less swelling and bleeding ( p < .05), mainly in the first 48 h. PBMT group presented a significantly higher palatal wound closure at 7 days compared to placebo group (33.41 vs. 21.20 respectively, p = .024) after adjustment for confounding. No adverse effects were reported. Conclusions: Photobiomodulation therapy accelerated the pain resolution time and palatal closure, decreased rescue medication consumption and significantly improved patient satisfaction in the postoperative period.